(untitled) (Scientific journal of the Fergana State University, 2025)
Communication is, first and foremost, an exchange of emotions, which can also serve as a motivating tool to initiate, continue, or stop communication. Accordingly, the study of "emotions" is also crucial from a pragmatic perspective, for example, in conducting conflict-free and dispute-free dialogues or in influencing listeners during a conversation. Since emotional impact in speech is embedded in the lexical and syntactic means of any language, the rapidly developing fields of text linguistics and pragmalinguistics demand the study of the unique characteristics of dialogic speech. The article thoroughly examines and interprets the types of sentences expressing emotions in English. Exclamative sentences belong to the earliest forms of speech that appeared in human history. Perhaps this is what makes their study so interesting.